"So Firm A Foundation": What The Comparative Study Of Religion Offers Positive Psychology - Maltby, Lauren E. (Research in the social scientific study of religion, 2008)
We undertake Haidt’s (2003) recommendation to positive psychology researchers to look to other cultures and eras for guidance in understanding some of Peterson and Seligman’s "ubiquitous, if not universal, virtues" (2004, p. 33). We propose that religion is a fertile ground for study by positive psychologists, and may be one area where "common denominators" or mechanisms of producing character strengths and virtues may be unearthed through more systematic study. To demonstrate this, we pose hypothetical relationships between Hinduism, Christianity, Islam, and Judaism and the character strengths of transcendence and justice (as typed by Peterson and Seligman, 2004), directly linking theological and cultural beliefs to the development of transcendence and justice. In so doing, we hope to open up new channels of communication between researchers in positive psychology and the psychology of religion.